The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/jonm.12656
|View full text |Cite
|
Sign up to set email alerts
|

Sleep problems in shift nurses: A brief review and recommendations at both individual and institutional levels

Abstract: With better awareness and understanding of shift nurses' sleep behaviours, effective interventions can be employed to improve shift nurses' sleep patterns and sleep quality to promote better emotional and health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
93
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(113 citation statements)
references
References 56 publications
11
93
1
8
Order By: Relevance
“…We can make a few suggestions here. For example, to partially improve CS, sleep enhancing practices should be promoted among nurses, such as less caffeine intake, night shifts to be scheduled in a reasonable pattern, cutting night shifts into shorter durations, offering nurses official sleeping naps during night shifts [44], establishment of a supportive climate within the unit, providing physical exercise services and a nice eating healthy facilities within the hospital setting [47]. Children and old age day and night care services can be offered for nurses in manageable fees, in an attempt to minimize family care burdens and increase nurses available rest time.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…We can make a few suggestions here. For example, to partially improve CS, sleep enhancing practices should be promoted among nurses, such as less caffeine intake, night shifts to be scheduled in a reasonable pattern, cutting night shifts into shorter durations, offering nurses official sleeping naps during night shifts [44], establishment of a supportive climate within the unit, providing physical exercise services and a nice eating healthy facilities within the hospital setting [47]. Children and old age day and night care services can be offered for nurses in manageable fees, in an attempt to minimize family care burdens and increase nurses available rest time.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Shift work has significantly changed nurses' sleep patterns, between 57% and 83.2% [16,17]. Poor sleep quality and insufficient sleep have an injurious effect on both the health and performance of nurses [18]. The results of this study suggest that there were significant differences in sleep quality between three different types of shift rotation, as measured by AIS.…”
Section: Discussionmentioning
confidence: 68%
“…Five of the eight factors of the OFER15 scale showed significant differences. Rotating shifts change frequently from day to night-shifts and most nurses working night-shifts struggle to adjust to daytime activities or normal night sleep patterns on their days off [18]. In this study, nurses had the best total sleep time and daytime performance on the two-shift fast rotation pattern, followed by the three-shift fast rotation and then the night-shift slow rotation patter.…”
Section: Discussionmentioning
confidence: 71%
“…Second, reducing rumination might be an effective way to increase nurses' sleep quality. Sun et al conducted a review of articles published up to 2016 that examined interventions on nurses' sleep problems and reported that methods of managing nurses' mental health have not been extensively reported in empirical research. Furthermore, most hospitals did not provide mental health services to nurses .…”
Section: Discussionmentioning
confidence: 99%